A true scribe of Abydos : essays on first millennium Egypt in honor of anthony Leahy - Leahy, Anthony, 1950-; Jurman, Claus.; Bader, Bettina.; Aston, David A. (Orientalia Lovaniensia analecta, 2017)
This book comprises twenty-two articles devoted to First Millennium Egypt, all intended to honour Antony Leahy, whose interest in this period is well known to scholars of this period. Both archaeology and philology are represented in this volume as well as studies on history and material culture. The interlocking interpretation of texts and objects is also noteworthy. The paper by Karl Jansen-Winkeln re-examines the question of the Libyan or Egyptian nature/origin/ethnic identity of the Third Intermediate Period, whilst others are more specific in their scope. Chronological discussions concerning the order of the kings of the 25th Dynasty in Egypt and Nubia are presented by Gerard Broekman and Roberto Gozzoli. Several objects belonging to a king Djehutyemhat are described by Troy Sagrillo.